Compensation for Phonological Assimilation in Bilingual Children. Issue 2 (2nd April 2020) - Carbajal, M. Julia; Chartofylaka, Lamprini; Hamilton, Mollie; Fiévet, Anne-Caroline; Peperkamp, Sharon
ABSTRACT: We investigate bilingual children's perception of assimilations, i.e. phonological rules by which a consonant at a word edge adopts a phonological feature of a neighboring consonant. For instance, English has place assimilation (e.g., green is pronounced with a final [m] in green pen ), while French has voicing assimilation (e.g., sac is pronounced with a final [g] in sac vert "green bag"). Previous research has shown that French and English monolingual toddlers compensate for the assimilation rule of their language, correctly recovering the intended words, but not for a rule that does not exist in their language. Using a word recognition videogame with French sentences, we show that French-English bilingual 6-year-olds perform exactly like French monolinguals of the same age: they compensate for voicing but not for place assimilation. Thus, despite their dual language input they have acquired French voicing assimilation and show no interference from English place assimilation.